Polycyclic aromatic hydrocarbons regulate the pigmentation pathway and induce DNA damage responses in keratinocytes, a process driven by systemic immunity. Issue 2 (November 2021) - Chan, Tze Khee; Bramono, Diah; Bourokba, Nasrine; Krishna, Vedula; Wang, Siew Tein; Neo, Boon Hoe; Lim, Rebecca Y.X.; Kim, Hyoju; Misra, Namita; Lim, Shawn; Betts, Richard J.
Highlights: BaP regulates pigmentation via activation of systemic immunity and the AhR pathway. BaP-activated PBMC induce DNA damage and POMC secretion in keratinocytes. Parental BaP does not induce cellular damage or stimulate the pigmentation pathway. Antioxidants enhance the genome protection and depigmentation effects of Dexamethasone. Abstract: Background: Urban pollution is correlated with an increased prevalence of skin pigmentation disorders, however the physiological processes underlying this association are unclear. Objectives: To delineate the relationship between polycyclic aromatic hydrocarbons (PAHs), a key constituent of atmospheric pollution, and immunity/skin pigmentation pathways. Methods: We exposed peripheral blood mononuclear cells (PBMC) to PAHs and performed cytokines/chemokine profiling. We then examined the effect of immune activation on pigmentation by co-culturing PBMC and Benzo(a)pyrene (BaP) with reconstructed human pigmented epidermis (RHPE). To study the mechanism, we treated keratinocytes with conditioned medium from BaP-exposed PBMC and studied DNA damage responses, aryl hydrocarbon receptor (AhR) activation and pro-pigmentation factor, proopiomelanocortin (POMC) secretion. Results: PAHs induced up-regulation of inflammatory cytokines/chemokine in PBMC. Co-culturing of RHPE with PBMC+BaP resulted in increased melanin content and localization. BaP-conditioned medium significantly increased DNA damage, p53 stabilization, AhR activation and POMC secretion in keratinocytes. We found that IFNγ induced DNA damage, while TNFα and IL-8 potentiated POMC secretion in keratinocytes. Importantly, BaP-conditioned medium-induced DNA damage and POMC secretion is prevented by antioxidants vitamin E, vitamin C and sulforaphane, as well as the prototypical corticosteroid dexamethasone. Finally, vitamin C and sulforaphane enhanced the genome protective and depigmentation effects of dexamethasone, providing proof-of-concept for a combinatorial approach for the prevention and/or correction of PAH-induced pigment spots formation. Conclusion: Our study reveals the importance of systemic immunity in regulating PAH-induced skin pigmentation, and provide a new keratinocyte DNA damage response mechanistic target for the prevention or reversal of pollution-associated skin pigmentation.